A very rare case of incidental aortic valve fibrolipoma. (12th October 2021) - Karsan, Rickesh Bharat; Kelly, Ronan; Healy, Estelle; Jeganathan, Reuben
Abstract: Cardiac valve fibrolipomas are extremely rare. We report a case of a 38-year-old female initially presenting with palpitations and moderate aortic incompetence who was found to have a lipomatous growth of the aortic valve. She underwent aortic valve repair with good postoperative results. Histopathogy verified the lesion as a fibrolipoma. This is the first reported case of fibrolipoma in the aortic valve, whilst aiming to consider repair as a surgical option in young patients with such growths. Abstract : Primary cardiac tumours are rare with a 0.5% incidence, of these 75% constitute benign pathologies including fibromas, fibroelastomas and haemangiomas [1].